The independent effects of hypovolaemia and pulmonary vasoconstriction on ventricular function and exercise capacity during acclimatisation to 3800 m. (6th June 2018) - Stembridge, Mike; Ainslie, Philip N.; Boulet, Lindsey M.; Anholm, James; Subedi, Prajan; Tymko, Michael M.; Willie, Christopher K.; Cooper, Stephen‐Mark; Shave, Rob
Abstract : Key points: We sought to determine the isolated and combined influence of hypovolaemia and hypoxic pulmonary vasoconstriction on the decrease in left ventricular (LV) function and maximal exercise capacity observed under hypobaric hypoxia. We performed echocardiography and maximal exercise tests at sea level (344 m), and following 5–10 days at the Barcroft Laboratory (3800 m; White Mountain, California) with and without (i) plasma volume expansion to sea level values and (ii) administration of the pulmonary vasodilatator sildenafil in a double‐blinded and placebo‐controlled trial. The high altitude‐induced reduction in LV filling and ejection was abolished by plasma volume expansion but to a lesser extent by sildenafil administration; however, neither intervention had a positive effect on maximal exercise capacity. Both hypovolaemia and hypoxic pulmonary vasoconstriction play a role in the reduction of LV filling at 3800 m, but the increase in LV filling does not influence exercise capacity at this moderate altitude. Abstract: We aimed to determine the isolated and combined contribution of hypovolaemia and hypoxic pulmonary vasoconstriction in limiting left ventricular (LV) function and exercise capacity under chronic hypoxaemia at high altitude. In a double‐blinded, randomised and placebo‐controlled design, 12 healthy participants underwent echocardiography at rest and during submaximal exercise before completing a maximal test to exhaustion at sea level (SL; 344 m) and after 5–10 days at 3800 m. Plasma volume was normalised to SL values, and hypoxic pulmonary vasoconstriction was reversed by administration of sildenafil (50 mg) to create four unique experimental conditions that were compared with SL values: high altitude (HA), Plasma Volume Expansion (HA‐PVX), Sildenafil (HA‐SIL) and Plasma Volume Expansion with Sildenafil (HA‐PVX‐SIL). High altitude exposure reduced plasma volume by 11% ( P  < 0.01) and increased pulmonary artery systolic pressure (19.6 ± 4.3 vs . 26.0 ± 5.4, P  < 0.001); these differences were abolished by PVX and SIL respectively. LV end‐diastolic volume (EDV) and stroke volume (SV) were decreased upon ascent to high altitude, but were comparable to sea level in the HA‐PVX trial. LV EDV and SV were also elevated in the HA‐SIL and HA‐PVX‐SIL trials compared to HA, but to a lesser extent. Neither PVX nor SIL had a significant effect on the LV EDV and SV response to exercise, or the maximal oxygen consumption or peak power output. In summary, at 3800 m both hypovolaemia and hypoxic pulmonary vasoconstriction contribute to the decrease in LV filling, but restoring LV filling does not confer an improvement in maximal exercise performance. Key points: We sought to determine the isolated and combined influence of hypovolaemia and hypoxic pulmonary vasoconstriction on the decrease in left ventricular (LV) function and maximal exercise capacity observed under hypobaric hypoxia. We performed echocardiography and maximal exercise tests at sea level (344 m), and following 5–10 days at the Barcroft Laboratory (3800 m; White Mountain, California) with and without (i) plasma volume expansion to sea level values and (ii) administration of the pulmonary vasodilatator sildenafil in a double‐blinded and placebo‐controlled trial. The high altitude‐induced reduction in LV filling and ejection was abolished by plasma volume expansion but to a lesser extent by sildenafil administration; however, neither intervention had a positive effect on maximal exercise capacity. Both hypovolaemia and hypoxic pulmonary vasoconstriction play a role in the reduction of LV filling at 3800 m, but the increase in LV filling does not influence exercise capacity at this moderate altitude.